2014
DOI: 10.1111/1750-3841.12470
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Trace Metals and Perfluorinated Compounds in 43 Representative Tea Products from South China

Abstract: This paper reports trace metals, and perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA) in wide range of tea products produced in the south China area. This paper also warns the low PFOS and PFOA pollution in tea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
5
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 25 publications
(32 reference statements)
3
10
5
2
Order By: Relevance
“…One study reported lead concentrations in liquid coffee of 2.37 and 2.57 μg/L (Ong 2014), and another study reported lead concentrations below the limit of detection of 1.5 μg/L (Ashu and Chandravanshi 2011). Additionally, studies have reported lead in tea leaves or residues from tea infusions of 0.046 to 15.479 μg/g (Li et al 2015;Shekoohiyan et al 2012;Shokrzadeh et al 2008;Onianwa et al 1999;Othman 2010;Al-Othman et al 2012;Zheng et al 2014). Although we did not detect any lead in our direct tap water or boiled tap water control samples, the presence of lead in drinking water is a known concern, as shown by the recent state of emergency issued in Flint, Michigan, because of its drinking water lead content.…”
Section: Discussioncontrasting
confidence: 61%
“…One study reported lead concentrations in liquid coffee of 2.37 and 2.57 μg/L (Ong 2014), and another study reported lead concentrations below the limit of detection of 1.5 μg/L (Ashu and Chandravanshi 2011). Additionally, studies have reported lead in tea leaves or residues from tea infusions of 0.046 to 15.479 μg/g (Li et al 2015;Shekoohiyan et al 2012;Shokrzadeh et al 2008;Onianwa et al 1999;Othman 2010;Al-Othman et al 2012;Zheng et al 2014). Although we did not detect any lead in our direct tap water or boiled tap water control samples, the presence of lead in drinking water is a known concern, as shown by the recent state of emergency issued in Flint, Michigan, because of its drinking water lead content.…”
Section: Discussioncontrasting
confidence: 61%
“…Maybe because leaf accumulation was caused by transpiration, perhaps the PFAAs come from the air. One paper on analysis of PFAAs in 43 tea products from South China found that PFOA content was higher than that of PFOS, and the highest concentration of PFOA was 0.25 ng·g −1 dry weight [13], compared with the concentrations in stem and bean vegetables.…”
Section: Resultsmentioning
confidence: 99%
“…The agricultural environment is polluted by PFAA perhaps due to the long range transport pathway, agricultural water irrigation and use of biosolids-amended soils [11]. Several field investigation papers have reported that PFAAs were widely detected in agricultural products (tea, cereals, salt, sweets, vegetables and fruit items) with PFOA showing a higher concentration [12,13,14,15]. Clark et al found the concentration of PFOA and PFOS in vegetables from the UK was up to 1000 pg·kg −1 ·ww.…”
Section: Introductionmentioning
confidence: 99%
“…However, tea contains some undesirable trace elements (heavy metal ions) and organic compounds, such as oxalate. The main sources of heavy metals in tea such as Pb and Cd are fertilizers and local environmental factors [ 8 ]. Chen et al [ 9 ] reported that Pb availability increased significantly as the soil pH decreased.…”
Section: Introductionmentioning
confidence: 99%